Nutrient consumption and digestibility in Garut sheep fed with elephant grass and pollard bran - Ningrum, T. W.; Hanim, C.; Yusiati, L. M.; Kustantinah, Kustantinah; Widyobroto, B. P. (2022)
This study aimed to compare the nutrients consumption and digestibility between Garut rams and ewes fed with forage (elephant grass) and concentrate (pollard bran) with a ratio of 60:40 (based on the dry matter). The livestock used were 6 Garut rams and 6 Garut ewes. They were placed in metabolic cages and equipped with feces containers. This research was conducted 14 days for the adaptation period and 5 days for the collection period. During the collection period, feed, feed residue, and feces collection were carried out for analysis. The analysis consisted of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), crude fiber (CF), nitrogen-free extract (NFE), and total digestible nutrients (TDN). The data obtained were used to calculate nutrient consumption and digestibility. Based on the research, it was known that average consumption and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), crude lipid (CL), crude fiber (CF), nitrogen-free extract (NFE), and total digestible nutrients (TDN) of Garut rams and ewes were not significantly different (P>0.05). All nutrients consumed by rams were higher than ewes, but the nutrients digestibility value in rams was lower than ewes. © Published under licence by IOP Publishing Ltd.